2014
DOI: 10.1016/j.brainres.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvements in sensory inhibition with gestational choline supplementation linked to α7 nicotinic receptors through studies in Chrna7 null mutation mice

Abstract: Perinatal choline supplementation has produced several benefits in rodent models, from improved learning and memory to protection from the behavioral effects of fetal alcohol exposure. We have shown that supplemented choline through gestation and lactation produces long-term improvement in deficient sensory inhibition in DBA/2 mice which models a similar deficit in schizophrenia patients. The present study extends that research by feeding normal or supplemented choline diets to DBA/2 mice carrying the null mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…A similar analysis was performed in a previous study in 50 children who were recorded as newborns but were not in the intervention trial (38). That study found significant effects of newborn P50 S2/S1 ratio on 40-month Child Behavior Checklist ratings for total problems and the anxious/depressed and attention subscales.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A similar analysis was performed in a previous study in 50 children who were recorded as newborns but were not in the intervention trial (38). That study found significant effects of newborn P50 S2/S1 ratio on 40-month Child Behavior Checklist ratings for total problems and the anxious/depressed and attention subscales.…”
Section: Resultsmentioning
confidence: 89%
“…In animal models, α7-nicotinic receptor activation is required for the effect of choline on inhibitory neurotransmission. In vitro, tissues derived from Chrna7 null mouse mutants do not show prenatal conversion of chloride transporter and development of inhibition; in vivo, Chrna7 null mutants do not respond to perinatal choline treatments with increased inhibition of the murine analog of human P50 responses (37, 38). A similar definitive test of the specific action of choline on α7-nicotinic receptors is not possible in humans.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of choline-supplementation include long-term improvements in sensory inhibition (Stevens et al, 2008, 2014), as well as attenuation of either in utero stress exposure (Schulz et al, 2014) or maternal immune activation (Wu et al, 2015) on both anxiety- and cognitive-related behaviors in adulthood. A recent study extended this research by feeding normal and supplemented choline diets, perinatally, to mice carrying the null mutation for the α7nACh receptor gene ( Chrna7 ) and demonstrated that the Chrna7 null-mutant failed to show behavioral improvements with choline-supplementation, strongly implicating functional α7nACh receptors as the mechanism (Stevens et al, 2014). However, additional mechanisms working in parallel with α7nACh receptor stimulation should be considered, including changes in gene expression, particularly DNA methylation, noted after choline supplementation during development (reviewed in Blusztajn and Mellott, 2012).…”
Section: Implications For Interventions In Psychiatric Disordersmentioning
confidence: 99%
“…α7-nicotinic acetylcholine receptor knockout mice (α7-nAChR KO) show deficits in sensory inhibition, working memory and attention, as well as reduced cortical expression levels of parvalbumin and NMDAR at adulthood(Fernandes et al 2006;Young et al 2007;Adams et al 2008). From 10 original manuscripts assessing this model, seven included males only, and two reported no sex differences, although limited sample sizes were used(Young et al 2011;Stevens et al 2014). In a molecular study by Adams and Stevens, male but not female α7-nAChR het mice showed reduced hippocampal GABA(A) receptor expression(Adams et al 2012).…”
mentioning
confidence: 99%